Examination Of the Effects of Ngo Concerning the Promotion of Youth Empowerment in Nigeria Rural Settings - Madinat Adefunke Olaniyan (Goodwood Publishing, 2026)
Purpose: This study aimed to examine the role of non-governmental organizations (NGOs) in promoting youth empowerment in rural Nigeria, particularly in Oyo town. Research Methodology: A descriptive survey design was used, with a two-stage sampling procedure for selecting participants. Data were collected using a structured questionnaire, and both face and content validity were ensured. Responses were analyzed using mean scores and standard deviation. Results: The findings revealed that NGOs play a significant role in providing entrepreneurship opportunities for rural youth, offering valuable resources, awareness, and skill-building programs. Key opportunities for NGOs include access to funding, collaboration with local communities, and capacity-building programs. However, challenges such as limited funding, lack of skilled staff, inadequate collaboration, and poor infrastructure limit the effectiveness of these NGOs. Rural youth perceive NGOs' role in facilitating entrepreneurship as essential for skill development, mentorship, and connecting them with funding opportunities. Conclusions: The study concludes that NGOs significantly contribute to youth empowerment in rural areas through training and mentorship programs. However, to maximize impact, NGOs must prioritize practical entrepreneurship training, provide tailored support for rural youth, and strengthen partnerships with other organizations. Limitations: The study is limited to Oyo town, which may restrict the generalizability of the findings to other rural regions in Nigeria. Additionally, challenges related to data collection may have impacted the accuracy of responses. Contributions: This study provides valuable insights into the role of NGOs in rural youth empowerment, offering practical recommendations for enhancing the effectiveness of NGO programs in fostering sustainable youth development.